Discursos, homofobia e políticas de direitos humanos - Oliveira, Cleide Ester de (2014)
This thesis has as a general aim to analyze the discourse produced by political and religious leaders according to what LGBT movement claims and public policies on human rights. We take as the theoretical background archeology and genealogy formulated by Michel Foucault to understand the theoretical categories: discourse, power / knowledge / truth, sexuality / homosexuality and standardization. We adopted qualitative approach to analyze the corpus that was videos posted on YouTube containing pronouncement, debate, lecture and preaching of six political and religious leaders opposed to the policies of human rights aimed at the LGBT group. The definition of participants number followed the data saturation criterion proposed by Minayo (2010). To analyze the discourses we used the DA (Gregolin, 2004), whose analysis proposal was outlined by Foucault and is based on the following categories: Who speaks? Where does it speak from? What effect of meaning does it produce? Which discourses appear (statements, contradictions, repetitions, regularities and dispersions)? What great event do the discourses emerge from? The data indicate that the discursive practices of religious and political leaders materialize in aversion, rejection and exclusion discourse. They also emerge discourses that relate to LGBT with deprived people of character, promiscuous, pedophiles and threatening the social order. In view of these leaders, human rights policies should not include LGBT group. The subjects are crossed by discourses of imprint moral, religious and pseudo-scientific that support the heteronormativity. Homophobia is institutionally legitimized if we consider the place where these subjects speak.